2009
DOI: 10.1111/j.1745-6592.2008.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Instantaneous Oxygen‐Limited Biodegradation of Petroleum Hydrocarbon Vapors in the Subsurface

Abstract: Petroleum hydrocarbon vapors biodegrade aerobically in the subsurface. Depth profiles of petroleum hydrocarbon vapor and oxygen concentrations from seven locations in sandy and clay soils across four states of Australia are summarized. The data are evaluated to support a simple model of biodegradation that can be used to assess hydrocarbon vapors migrating toward built environments. Multilevel samplers and probes that allow near-continuous monitoring of oxygen and total volatile organic compounds (VOCs) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 31 publications
8
88
0
Order By: Relevance
“…In the unsaturated zone, biodegradation of VOC occurs only in the aqueous phase and can be described by a variety of kinetic models (zero order, first order, Monod kinetics, or instantaneous bimolecular reaction). The last two apply to conditions of low oxygen partial pressure and reaction fronts of hydrocarbons with oxygen (Davis et al, 2005(Davis et al, , 2009). For fully aerobic conditions, Hohener et al (2003) explain how the kinetics of biodegradation is related to the VOC concentration in the gas phase, and how Henry's law is involved therein.…”
Section: Process Representation In the Modelmentioning
confidence: 99%
“…In the unsaturated zone, biodegradation of VOC occurs only in the aqueous phase and can be described by a variety of kinetic models (zero order, first order, Monod kinetics, or instantaneous bimolecular reaction). The last two apply to conditions of low oxygen partial pressure and reaction fronts of hydrocarbons with oxygen (Davis et al, 2005(Davis et al, , 2009). For fully aerobic conditions, Hohener et al (2003) explain how the kinetics of biodegradation is related to the VOC concentration in the gas phase, and how Henry's law is involved therein.…”
Section: Process Representation In the Modelmentioning
confidence: 99%
“…Evidence for vadose zone biodegradation of BTEX has been seen at several field studies reporting typical average values of biodegradation constant rates in the order of 0.01 and 10 d À1 (e.g. see Davis et al, 2009;DeVaull et al, 1997;Hers et al, 2000;Hoener et al, 2003). On the contrary, PAHs are largely sorbed to the soil and are slowly biodegradable.…”
Section: Risk Calculationmentioning
confidence: 94%
“…Finally it is worth noting that the first-order degradation rates used in the model to best fit the field data are achieved assuming values that are in line with those reported in the literature (e.g. Davis et al, 2009;DeVaull et al, 1997;Brauner et al, 2002;Blum et al, 2009;Bockelmann et al, 2001). Namely, as discussed before, typical average median values of biodegradation constant rates for BTEX are in the order of 0.01 and 10 d À1 whereas for PAHs are in the range of 0.0001e0.01 d À1 .…”
Section: Attenuation During Leachingmentioning
confidence: 95%
“…Nonaqueous-phase liquid (NAPL) contaminants introduced into the unsaturated zone spread as a liquid phase; however, they can also vaporize and migrate in a gaseous state. In particular, vapor (gas) plumes migrate easily in the unsaturated zone (Barber and Davis, 1991;Davis et al, 2005Davis et al, , 2009Höhener et al, 2006;Brusseau et al, 2013). When assessing the danger of groundwater contamination by downwardmigrating vapor plumes, retention effects on transport are of major interest.…”
Section: Introductionmentioning
confidence: 99%
“…Corley et al (1996) showed that low concentrations of volatile organic compounds distribute in the bulk phases (air, water, and solid), adsorb to the air-water interface, and partition into intraparticle pores in unsaturated and saturated porous media. While it has been demonstrated in experiments that the gas-water interface poses a high potential for retardation (Brusseau et al, 1997;Costanza-Robinson and Brusseau, 2002b), determining the effective interfacial area, which controls the contaminant mass transfer, is still subject of intensive research (Goss, 2009;Kibbey and Chen, 2012;Brusseau et al, 2015). Mayes et al (2003) stated that immobile water in pores could act as a short-term sink and as a long-term source of potential contaminants.…”
Section: Introductionmentioning
confidence: 99%